Using author-devised cover letters instead of instructor-devised rubrics to generate useful written peer feedback comments - Yallop, Roger; Leijen, Djuddah A. J. (Journal of Academic Writing, 2021)
This study uses both qualitative and quantitative research methods in a mixed-methods approach to investigate whether the principled use of author-devised cover letters (CLs) within doctorate writing groups can result in more useful reviewer feedback comments than would be attained through the use of instructor-devised writing assessment rubrics. In this context, CLs are self-devised written documents that help the reviewers give the author useful and critical written feedback comments. Twenty participants in different discipline-specific writing groups were given explicit instruction about the importance and content of CLs during the peer feedback process. Their perceptions of a useful CL were obtained from post-course questionnaires and analysed qualitatively. In addition, their CLs at various stages of the feedback process were analysed quantitatively for genre, social presence, and evidence of teaching instruction, and compared to the CLs produced by 20 PhD students in similar writing groups who received minimal CL instruction. The study found that author-devised CLs, as opposed to instructor-devised rubrics, can allow the authors the flexibility of providing text-specific background details, requesting reviewer help on specific textual aspects, using social presence to develop a sense of writing community, and provide reflection upon their own writing.